Democracia em preto e branco : futebol, política e rock n' roll - Muhlenberg, Arthur; Lee, Rita (TvZero, 2014)
The film investigates a fascinating period in Brazilian history, the transition from dictatorship to democracy, through three narratives: the popular demands for free elections, the growth of Brazilian rock groups and the revolutionary football movement (led by legendary player Sócrates) known as Corinthian democracy. --